1998
DOI: 10.1177/152660289800500402
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty and Stenting of the Extracranial Carotid Arteries

Abstract: We performed percutaneous transluminal angioplasty and stenting in patients with carotid artery stenosis to determine the efficacy of these techniques as an alternative to surgical endarterectomy.From April 1995 through July 1999 carotid angioplasty procedures were performed (right, 151; left, 164)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
55
1
4

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 48 publications
1
55
1
4
Order By: Relevance
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,17,26,27 The reported rate of severe bilateral carotid stenosis and/or occlusion varies widely (3.2%-39%) 8,9,17,28 and was encountered in 14.6% of the patients at high surgical risk in our prospective CAS data base. Although bilateral carotid stenosis has been shown to potentially increase the risk for complications during CEA or CAS and has been included as 1 of the high risks for CEA, our data revealed that there was no significant difference in outcome at 30 days or at 6 months between the bilateral and unilateral stent-placement patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Since Mathur et al 6 first reported the feasibility of staged CAS for bilateral carotid stenosis, some small series have been published in an attempt to promote staged or simultaneous revascularization. [7][8][9][10][11][12][13][14][15][16] However, the results have been equivocal, and there is an obvious need for larger trials to firmly establish the superiority of the simultaneous or the staged approach. Nonetheless, patients with bilateral carotid artery disease have been excluded from most prospective trials due to concerns regarding possible complications and/or poor outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although effective in reducing embolic phenomena, this method causes a temporary interruption in cerebral blood flow, which is not always well tolerated by patients (especially in the presence of contralateral carotid occlusion or anomalies in the circle of Willis). The good results initially reported by Theron et al could not be universally reproduced, and several cases of cerebral ischemia resulting from the use of this system were reported 19,21 . In addition, operational technical difficulties made it less and less used.…”
Section: Discussionmentioning
confidence: 86%
“…rotid disease and severe flow obstruction close to the angle of mandible, inaccessible to surgery; those with radical dissection of the neck followed by radiation therapy (the cases of cervical neoplasias, for example); those with restenosis after carotid endarterectomy; and those with fibromuscular dysplasia 12,21 .…”
Section: Discussionmentioning
confidence: 99%